Effects of long-term maize/peanut intercropping and phosphorus application on soil surface electrochemical properties and crop yield - Ma, Rentian; Yu, Ning; Zhao, Shiwei; Kou, Taiji; Jiao, Nianyuan (Frontiers in Agronomy, 2025)
Intercropping and phosphorus application are effective ways to increase crop yield and improve cultivated land quality. This study took the soil under the maize-peanut intercropping system which has been planted for 12 years as the research object, the physical, chemical, and electrochemical properties of soil, and crop yield under different planting patterns [sole-crop maize (SM), sole-crop peanut (SP), and maize-peanut intercropping (M/P)] and phosphorus application rates [P application (180 kg P2O5 ha−1) and no P application (0 kg P2O5 ha−1)] were studied. The results showed that intercropping increased soil aggregate stability, clay content, and gas phase ratio, P application further optimized the soil physical properties. At the same time, intercropping decreased soil pH and EC, increased soil organic carbon (SOC), total nitrogen (TN), and total phosphorus (TP) contents. P application increased soil pH, SOC, TN, TP, and EC. Compared with monoculture, intercropping increased the surface charge number (SCN) by 19.98%, specific surface area (SSA) by 44.34%, surface charge density (σ0) by 38.08, electric field strength (E0) by 38.22, and Zeta potential by 46.85%. P application further increased the SCN by 20.75%, SSA by 23.43%, σ0 by 67.82%, E0 by 67.13%, and Zeta potential by 15.51%. Maize-peanut intercropping increased the total crop yield of the intercropping system, the application of phosphate fertilizer further increased the yield of maize and peanut. The aggregate stability and nitrogen were significantly positively correlated with crop yield, and the carbon, phosphorus, and electrochemical properties were extremely significantly positively correlated with crop yield.